تطوير دور مصرف سورية المركزي لرفع كفاءة محاسبة الدين العام - القاضي, حسين; العمار, رضوان; هاشم, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يمثل الدين العام القائم في فترة معينة حجم الاقتراض السابق لتلك الفترة والذي لم يسدّد بعد. وينشأ الدين العام كنتيجة لتمويل عجز الموازنة العامة للدولة بالاقتراض ، وتقترض الحكومات محلياً من المصارف التجارية أو المصرف المركزي أو من المؤسسات المالية وغير المالية بالإضافة إلى الجمهور . كما تقترض الحكومات من الخارج من خلال الأسواق الدولية من المؤسسات الخاصة أو العامة أو الاقليمية أو الدولية ، ويكوّن الاقتراض سواء أكان محلياً أم خارجياً تكلفة يتحدد مقدارها بسعر الفائدة وحجم الاقتراض ، وعادة ما يكون حجم الاقتراض بمقدار تمويل العجز في الموازنة . ويأتي هذا العجز مصاحباً لتوسع النفقات العامة بأكثر من زيادة الإيرادات العامة حيث تلجأ الدولة إلى الأساليب النقدية التي تتمثل أساساً في الإصدار النقدي لتغطيتها أي لجوئها إلى عقد القروض العامة . وفي بحثنا هذا قمنا بدراسة الدَّين العام في سورية بشقيه الداخلي والخارجي كما واطلعنا على مديرية الدَّين العام في وزارة المالية كونها الجهة المسؤولة قانونياً عن إدارته ، ومن ثم تعرّفنا على دور مصرف سورية المركزي في إدارة الدّين العام وماهي السبل التي تتيح تفعيل دوره لرفع كفاءة محاسبة الدَّين العام . The general debt of a particular period represents the unpaid amount of borrowing prior to that period. General debt is caused by financing the deficit in government budget through borrowing from local, regional, or foreign banks and financial institutions, as well as from certain members of the public. Borrowing becomes a burden whose cost is determined by both the amount of interest and size of borrowing. Borrowing itself is generally relative in size to the budget deficit. The deficit is due to imbalance between government spending and government revenues. To face this situation, the government resorts to fiscal methods, including issuing money or borrowing. This study examines public borrowing in Syria, both from local and external sources. We were given access to the department of public borrowing in the Ministry of Finance, being the body legally responsible for administration of borrowing. Then, we have been acquainted with the role of the Central Bank in administering public debt and with the ways to activate that role and raise competence of general debt accounting.